The Bidayuh language as a threatened language - Norahim, Norazuna (Universiti Malaysia Sarawak (UNIMAS), 2013)
The aim of this paper is to report the findings of a larger study that investigates variability of language choice patterns across generations among the Bidayuh in urban settings - Kuching-Samarahan Division, Sarawak. A major aim of the study was to ascertain the existence of an on-going language shift within the community, and to describe the process of language shift. Unlike previous studies on Language shift and Language maintenance (LSLM) that focused on small communities in the region, this study examined an ethnic minority community with a population of approximately 204,800 (Population Census, 2009). The scope of the study was restricted to educated Bidayuh as it was not feasible to conduct a language shift study that was representative of the total population. It would involve several demographic variables.